PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM SEKOLAH TERHADAP MOTIVASI BERPRESTASI GURU SEKOLAH KHUSUS DI KOTA PONTIANAK - Setiawan, Ady; Sukmawati, Sukmawati; Chiar, M. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to determine how the teachers’ achievement motivation, the principals’ transformational leadership, and school climate, also how the influence of each and simultaneously all variables. The general objective of this research is to determine the influence of transformational leadership and school climate on the achievement motivation of teachers in special schools in Pontianak, Indonesia. This research uses quantitative research methods and uses a questionnaire as a data collection tool. The subjects of this study were 65 teachers of special schools in elementary schools (SDLB) in Pontianak. Their characteristics are permanent teachers, a minimum of two years of work, status as government employees or non, and a bachelor’s degree. The results of the study are: (1) a description of teachers’ achievement motivation is classified as high (34.38%) and variations score 92-99; (2) the description of transformational leadership is quite good (45.32%) and variations score 110 - 122; (3) the description of special school climate is classified as good (39.06%) and variations score 103-110; (4) transformational leadership influences the teachers’ achievement motivation; (5) school climate influences teachers’ achievement motivation; and (5) simultaneously, transformational leadership and school climate influence teachers’ achievement motivation. The conclusion of this study is the achievement motivation of special school teachers in Pontianak is influenced by the principals’ transformational leadership and school climate by 39.50% simultaneously, while the other 60.50% is influenced by other variables. Keywords: Achievement Motivation, School Climate, Transformational Leadership